Islamic architecture a visual analysis of the architectural elements of the masjid (mosque) in Cotabato City - Mastura, Bai Charlene C. (2018)
The majority of Cotabato City?s current population is Muslim, comprising about 80% of the population. Muslims perform As?-S?ala?h ? one of the five pillars of Islam, the prescribed prayers which have to be offered five times a day. The As?-S?ala?h is performed in the Masjid. This means that this place of worship is important to the Muslims as it is used regularly. The abundance of Masajid in Cotabato City is the effect of numerous Muslims residing in the area. The NCAA has documented several stunning Masajid with the title ?Mosque/Masjid Architecture: Jewels of Philippine Islamic Faith?. Hence, only three Masajid in Cotabato City were documented among the numerous Jami Masajid in the area. There are neither specific, definite and detailed instruction written in the Qur?a?n regarding the architectural form of a Masjid and its worship space, nor there are any building requirements specified in the Sharia law. In this connection, this study aimed to map the locations of the Masajid (specifically Jami Masajid) around Cotabato City, document the history of the design of each architectural element and to document the elements of each Masjid through historical timeline. The results of the most common architectural elements evident in this study underwent visual analysis through historical timeline, tabulation and frequency and percentage distribution to evaluate the most common architectural elements of Masajid in Cotabato City. This study also tried to prove the relationship between the history of Islamic Architecture and the local culture of the community. In addition, this study showed the historical continuity through Islamic architecture relating the architectural elements of the past up to the current time. As a conclusion, this study aimed to define the cultural, historical and spiritual identity of Muslim Cotabaten?os and the city itself.